A lusofonia e uma concepção de política linguística - Casagrande, Nancy dos Santos (2011)
This article aims at discussing the linguistic politics accomplished in different periods of time concerning lusophone issues. Therefore, conceptions of Linguitic Politics and Lusophony, as well as the relationship between ideology and cultural imposition are subjects of interest in this study. In this sense, it is responsibility of the State the formation of the individual on the subject of critical minds; it is claimed as mandatory the understanding of the notion that language, communication and culture are intertwined, a truism, when the purpose is the mastery of either the mother or the foreign language and, above all, the implementation of a method of learning and teaching that respects such vision.